Stratégies de lecture en français L1 et en anglais L2 chez des universitaires diplômés : aspects quantitatifs - de Serres, Linda (Canadian Journal of Applied Linguistics, 2003)
This paper reports on a study investigating reading strategies used by 16 French-speaking university students, all of whom were good readers. Variables such as linguistic proficiency and reading proficiency were considered in French (L1) and in English (L2). Through introspective verbal reports, two different groups of eight readers expressed their strategies while reading abstracts of expository texts, one in L1 and one in L2. All readers evidenced familiarity with a variety of strategies. Five different categories were considered: global, local, technical, diverse and parallel. Overall, the total number of strategies reported in each group did not differ significantly. However, in L2, under the category of local strategies, we notice a significant difference between the two groups. Some explanations are provided for this difference, including a low level of English proficiency and a lack of automatization of strategies.